Digital Communication Strategy of Bukit Kaba Tourism Through Social Media Based on IMC and AIDA - R. Muhammad Ihsan; Elyusra (LPPM Stikosa - AWS, 2025)
The use of social media in tourism communication strategies has become crucial in the digital era. Bukit Kaba, a nature-based tourism destination in Bengkulu, utilizes platforms such as Instagram, Facebook, and TikTok for promotion. However, the extent to which these platforms are strategically and integratively employed remains underexplored. This study aims to analyze the digital communication strategy of Bukit Kaba’s tourism management through social media by applying the Integrated Marketing Communication (IMC) and Attention, Interest, Desire, Action (AIDA) theoretical frameworks. A qualitative descriptive method was employed, using digital observation, documentation, and in-depth interviews. The findings reveal that each platform demonstrates unique characteristics and communication performance. TikTok exhibits strong engagement but lacks persuasive storytelling; Instagram excels in visuals but lacks explicit calls to action; Facebook is more informative yet less frequently updated. None of the platforms present a fully integrated cross-platform messaging strategy. These results highlight the need for IMC-based consistency reinforcement and better AIDA-driven content planning to attract, engage, and mobilize potential tourists. This study contributes to the development of social media–based digital communication models for tourism destinations and offers practical recommendations for tourism managers in designing effective and sustainable promotional strategies.